2015
DOI: 10.1371/journal.pone.0116646
|View full text |Cite
|
Sign up to set email alerts
|

A Key ABA Catabolic Gene, OsABA8ox3, Is Involved in Drought Stress Resistance in Rice

Abstract: Expressions of ABA biosynthesis genes and catabolism genes are generally co-regulated in plant development and responses to environmental stress. Up-regulation of OsNCED3 gene, a key gene in ABA biosynthesis, has been suggested as a way to enhance plant drought resistance but little is known for the role of ABA catabolic genes during drought stress. In this study, we found that OsABA8ox3 was the most highly expressed gene of the OsABA8ox family in rice leaves. Expression of OsABA8ox3 was promptly induced by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 45 publications
7
36
0
Order By: Relevance
“…2B and 3, B and C) is similar to what was found for SDIR1, another RING-H2 protein implicated in the positive regulation of ABA signaling . A recent study showed that in rice, achieving higher ABA levels through down-regulation of OsABA8ox3 using an RNAi strategy can improve drought stress resistance (Cai et al, 2015). These results are consistent with our finding that ZmXerico1 reduces protein stability of specific ZmABA8ox in vivo, such as maize ortholog of OsABA8ox3, ZmABA8ox3a, leading to increased drought tolerance.…”
Section: Zmxerico1 Functions As An E3 Ubiquitin Ligase and Its Overesupporting
confidence: 92%
“…2B and 3, B and C) is similar to what was found for SDIR1, another RING-H2 protein implicated in the positive regulation of ABA signaling . A recent study showed that in rice, achieving higher ABA levels through down-regulation of OsABA8ox3 using an RNAi strategy can improve drought stress resistance (Cai et al, 2015). These results are consistent with our finding that ZmXerico1 reduces protein stability of specific ZmABA8ox in vivo, such as maize ortholog of OsABA8ox3, ZmABA8ox3a, leading to increased drought tolerance.…”
Section: Zmxerico1 Functions As An E3 Ubiquitin Ligase and Its Overesupporting
confidence: 92%
“…ABA mediates plant germination and early seedling growth (Mulkey et al, 1983;Cornish and Zeevaart, 1985). Stimulating ABA biosynthesis inhibits seed germination as well as root and shoot growth in rice (Ikeda et al, 2002;Zhu et al, 2009;Cai et al, 2015). We found that seed germination was delayed in OE-OsDET1 plants and that root and shoot growth was inhibited during ABA treatment (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Plant respond and adapt to drought stress through various physiological and metabolic processes including stomatal closure, repression cell growth, photosynthesis and activation of respiration to increase the chance of survival [33]. The molecular mechanism drought stress tolerance is extremely complicated which is a multigene phenomenon in Arabidopsis plants [34]. Signal transduction in response of drought stress can be divided in to two pathway, ABA independent and ABA dependent pathway [35].…”
Section: Drought Stress Responsementioning
confidence: 99%